СПЕЦИФІКА ТА ЗМІСТ ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ В ОРКЕСТРОВОМУ КЛАСІ (Педагогіка вищої та середньої школи, 2006)
The article defines the role of the orchestral class in the system of the music teacher's professional training. The specific character and the content of the educational activities of the Art Department students of the Pedagogical I University in the chamber orchestra are covered in it.